F(x) = 3x -1
g(x) = x+2
so
(f+g)(x) = 3x -1 + x+2
(f+g)(x) = 4x + 1
answer is C. 4x + 1
Answer: ![x=\frac{3}{5}+i\frac{4}{5},\:x=\frac{3}{5}-i\frac{4}{5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%7D%7B5%7D%2Bi%5Cfrac%7B4%7D%7B5%7D%2C%5C%3Ax%3D%5Cfrac%7B3%7D%7B5%7D-i%5Cfrac%7B4%7D%7B5%7D)
Step-by-step explanation:
![25x^2-30x+25=0](https://tex.z-dn.net/?f=25x%5E2-30x%2B25%3D0)
![x_{1,\:2}=\frac{-\left(-30\right)\pm \sqrt{\left(-30\right)^2-4\cdot \:25\cdot \:25}}{2\cdot \:25}](https://tex.z-dn.net/?f=x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-%5Cleft%28-30%5Cright%29%5Cpm%20%5Csqrt%7B%5Cleft%28-30%5Cright%29%5E2-4%5Ccdot%20%5C%3A25%5Ccdot%20%5C%3A25%7D%7D%7B2%5Ccdot%20%5C%3A25%7D)
![\sqrt{\left(-30\right)^2-4\cdot \:25\cdot \:25}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-30%5Cright%29%5E2-4%5Ccdot%20%5C%3A25%5Ccdot%20%5C%3A25%7D)
![=\sqrt{30^2-4\cdot \:25\cdot \:25}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B30%5E2-4%5Ccdot%20%5C%3A25%5Ccdot%20%5C%3A25%7D)
![=\sqrt{30^2-2500}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B30%5E2-2500%7D)
![=i\sqrt{2500-30^2}](https://tex.z-dn.net/?f=%3Di%5Csqrt%7B2500-30%5E2%7D)
![=40i](https://tex.z-dn.net/?f=%3D40i)
![x_{1,\:2}=\frac{-\left(-30\right)\pm \:40i}{2\cdot \:25}](https://tex.z-dn.net/?f=x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-%5Cleft%28-30%5Cright%29%5Cpm%20%5C%3A40i%7D%7B2%5Ccdot%20%5C%3A25%7D)
![x_1=\frac{-\left(-30\right)+40i}{2\cdot \:25},\:x_2=\frac{-\left(-30\right)-40i}{2\cdot \:25}](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7B-%5Cleft%28-30%5Cright%29%2B40i%7D%7B2%5Ccdot%20%5C%3A25%7D%2C%5C%3Ax_2%3D%5Cfrac%7B-%5Cleft%28-30%5Cright%29-40i%7D%7B2%5Ccdot%20%5C%3A25%7D)
![x=\frac{3}{5}+i\frac{4}{5},\:x=\frac{3}{5}-i\frac{4}{5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%7D%7B5%7D%2Bi%5Cfrac%7B4%7D%7B5%7D%2C%5C%3Ax%3D%5Cfrac%7B3%7D%7B5%7D-i%5Cfrac%7B4%7D%7B5%7D)
The answer is 2
See 1 +0 is 1 so 1+1=2
Answer:
<u>4(1 – x) + 2 x = -3( x + 1)</u>
first do 4 time 1= 4
then do 4 times x =4x
now the equation should look like this
4-4x+2x=-3(x+1)
then do the other side of the equation
-3(x+1)
=-3x-3
Now collect the like terms:
-4x-2x
now the equation should look like this
4-2x=-3x-3
now add 3x add on both sides
4-2x+3x=-3
put the 4 on the other side
-2x+3x=-3-4
now again collect the like terms (-2x+3x=1 which is just x and -3-4 =-7)
x=-7
answer
x=-7